Internalizasi Akhlak Islam melalui Pendekatan Psikologi dalam Pembelajaran: Internalizing Islamic Morals through a Psychological Approach in Learning - Sarbini, Sarbini; Suhendi, Saca; Santora, Pipih; Nurhayati, Fitriani; Rosulina, Desi; Muttaqien, Qorie Hizratul; Astuti, Hofifah (Institut Agama Islam Daruttaqwa Gresik, 2025)
In the context of Indonesian elementary schools (SD), Islamic religious education often prioritizes rote memorization of moral teachings, yet struggles to foster deep internalization of Islamic morals amid modern social challenges. Rapid societal changes, including digital influences and peer pressure, highlight the need for a psychological lens to understand how students truly internalize values such as honesty, empathy, and responsibility. This gap underscores the urgency for research that bridges religious doctrine with developmental psychology to cultivate authentic character formation. This study aims to deeply explore the experience of internalizing Islamic morals through a psychological approach to learning in elementary schools (SD). Employing a qualitative phenomenological methodology, it illustrates that the internalization process engages not only cognitive aspects but also intrinsic motivation, profound emotional experiences, and intensive social interactions between students and teachers. The findings emphasize that integrating psychological dimensions into religious education is crucial for fostering authentic, sustainable moral character relevant to students’ social lives. The internalization process transcends cognition, engaging intrinsic motivation, profound emotional resonance (e.g., awe during Quranic reflections), and intensive teacher-student interactions. Key themes include “emotional awakening” via storytelling and “social mirroring” through role-modeling, revealing that psychologically attuned methods amplify moral embodiment. This study significantly contributes to the development of Islamic religious education models that cohesively combine developmental psychology theories with moral education. These findings advocate integrating developmental psychology theories (e.g., Bandura’s social learning) into Islamic education curricula, offering practical recommendations for educators—like emotion-focused activities and collaborative learning—and policymakers to Design humane, responsive strategies. This result fosters holistic character building, contributing to innovative, contextually relevant models for sustainable moral education in Indonesian SDs. Furthermore, it offers practical recommendations for educators and policymakers to Design humane, psychologically responsive learning strategies capable of creating conducive environments for the holistic character formation of students..